PENGARUH PENGAWASAN PIMPINAN TERHADAP EFEKTIVITAS PENERIMAAN RETRIBUSI TERMINAL DI UPTD PERHUBUNGAN CIBADAK - Rike Anggun Artisa (Mimbar Administrasi Mandiri, 2023)
The aims of this study are to find out: (1) How is the Supervision of Leaders at the UPTD Transportation Cibadak Sukabumi Regency. (2) How is the Effectiveness of Receipts for Receiving Terminals at the UPTD Transportation of Cibadak, Sukabumi Regency. (3) How big is the influence of leadership supervision on the effectiveness of receiving terminal fees at the Cibadak Transportation UPTD, Sukabumi Regency. The researcher used a quantitative approach, the sample used was 109 people from a population of 896 people taken by probability sampling technique with the Disproportionate stratified random sampling method and the Slovin formula as a tool. There are two variables studied in this study, namely (1) Leadership Supervision (X) and (2) Effectiveness of Receipt of Terminal Retribution (Y). The tool used in this study is a questionnaire with a rating scale of 5 (five) choices. The data collected was then analyzed using descriptive analysis techniques using item averages, while statistical analysis techniques used Pearson Product Moment (PPM) correlation analysis, and simple linear regression equation models. The calculation results show that the cumulative average value of the Leadership Supervision variable is 3.61, which is included in the good category, while the Effectiveness of Receipts for Terminal Retribution of 3.61 is included in the good category. The results of statistical analysis obtained the price of r_xy = 0.444 which is included in the fairly strong category with a significance value (2-tailed) 0.000 > 0.005 or t_count = 41.97 > t_table = 1.981 so that it can be concluded that Leadership Supervision has a positive and significant effect on the Effectiveness of Retribution Receipts. Terminal while the Coefficient of Determination (KD) is 0.9428, which means 94.28% of the Effectiveness of Terminal Retribution Receipts (Y) can be explained by the Leadership Supervision variable (X) and the rest is determined by other factors. Furthermore, the linear regression equation model is = 0.641 + 0.980X. Therefore, to improve the effectiveness of Terminal Retribution Receipts, it is suggested to the Chief Executive to improve the Supervision function.